Multi-level simulation in manufacturing companies: The water-energy nexus case. (15th December 2016) - Thiede, Sebastian; Schönemann, Malte; Kurle, Denis; Herrmann, Christoph
Abstract: Factories consist of production equipment, technical building services and a building shell, which are dynamically connected through energy and resource flows. An isolated analysis of flows cannot sufficiently consider the strong interdependencies and mutual relationship between resources. Because of that, it is relevant to acquire a sound understanding of conflicting and synergetic interactions between resources, in order to assess risks and to avoid problem shifting. The close intertwining of water and energy demand (water-energy nexus) in a factory exemplary represents a prominent relationship of coupled resources at all factory elements through different flows. To analyze and evaluate potential problem shifts as well as dynamic system/factory behavior, simulation has proven to be an appropriate method. However, simulation approaches often have a limited scope and address only isolated manufacturing system levels. Moreover, existing multi-level and multi-model approaches do not clearly state the method used for level selection, transferred parameters and coupling options for different models. This paper presents a multi-level simulation framework and recommendations for selecting coupling concepts. The recommendations refer to the simulation goals and the involved data to be exchanged between the different simulation models and factory elements. The framework supports developing coupled simulation models and it helps to address and assess problem shift issues. This is shown by exemplarily applying the framework in the context of the water-energy nexus of an automotive factory. The application reveals amplifying as well as attenuating effects of potential improvement measures on the water and energy demand indicating the importance of gaining a holistic factory perspective.